Eco culture : disaster, narrative, discourse - Bell, Robert C.; Ficociello, Robert (Ecocritical theory and practice., 2018)
"The edited collection, Eco Culture: Disaster, Narrative, Discourse, opens a conversation about the mediated relationship between culture and ecology. The dynamic between these two great forces comes into stark relief when a disaster--in its myriad forms and narratives--reveals the fragility of our ecological and cultural landscapes."--